2019
DOI: 10.1158/1538-7445.am2019-lb-200
|View full text |Cite
|
Sign up to set email alerts
|

Abstract LB-200: A cGMP-grade chimeric papillomavirus candidate vaccine (HPV16 RG1-VLP) confers long term cross-protection compared to a nonavalent hpv vaccine in a pre-clinical papillomavirus animal model

Abstract: Background: The National Cancer Institute (NCI) PREVENT Cancer Program (PREVENT) is a peer-reviewed R&D pipeline with the core emphasis on preclinical development and clinical translation of novel cancer preventive interventions. One of the latest PREVENT-supported projects include cGMP production and IND enabling studies of a broad spectrum experimental human papillomavirus (HPV) vaccine- HPV16 RG1-VLP. This monovalent chimeric virus-like particle (VLP) displays 360 copies of the highly conserved epitope … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Two previous studies investigated the immunological response of TA-GW combined with Alhydrogel ® to induce a T cell and a humoral response against L2 and E6. The limits of these data are the frequent spontaneous rate of regression of genital warts [ 65 , 66 ], but this research opens the way to use the treatment in laryngeal juvenile respiratory papillomatosis of children and in vulvar, vaginal and anal HPV lesions, where the treatment is often repetitive and surgical.…”
Section: Discussionmentioning
confidence: 99%
“…Two previous studies investigated the immunological response of TA-GW combined with Alhydrogel ® to induce a T cell and a humoral response against L2 and E6. The limits of these data are the frequent spontaneous rate of regression of genital warts [ 65 , 66 ], but this research opens the way to use the treatment in laryngeal juvenile respiratory papillomatosis of children and in vulvar, vaginal and anal HPV lesions, where the treatment is often repetitive and surgical.…”
Section: Discussionmentioning
confidence: 99%
“…Based upon these encouraging findings, RG1-VLP have been produced under cGMP sponsored by the US National Cancer Institute’s (NCI) PREVENT Cancer program [ 107 ] for a first in human multicenter phase I study scheduled to start in 2021.…”
Section: Rg1-vlpmentioning
confidence: 99%
“…We have sought to address this duration of protection question without the need of additional boosters. Utilizing RG1-VLP particles from engineering runs from the NCI PREVENT program, several recent in vivo studies in both mice and rabbits were performed [ 107 ]. For example, utilizing the cotton tail rabbit papillomavirus (CRPV) model, in a one year long head-to-head vaccine study against Gardasil-9, it was shown that vaccination with RG1-VLPs adjuvanted with aluminum hydroxide alone (Alhydrogel TM ) provided complete in vivo protection against nine different HPVs (HPV6,16,31,45,52,58,35,39,59).…”
Section: Rg1-vlpmentioning
confidence: 99%